Characteristics of pregnant women with chronic energy deficiency (CED) - Eny Setiawati; Puspitasari, Elika (Universitas 'Aisyiyah Yogyakarta, 2024)
Chronic energy deficiency (CED) is a condition of imbalance of energy and protein intake that can lead to pregnancy disorders such as anemia, bleeding, abnormal weight gain, and infection. This study aims to determine the characteristics of pregnant women with CEDs at the Galur II Kulon Progo Health Center. The research design used quantitative descriptive. The sample of this study was all pregnant women with CEDs as many as 49 respondents. The results showed that pregnant women with CEDs had age characteristics of 20-35 years (91.8%); have never given birth (51%); high school education level (61.2%); work as a housewife (67.3%); and did not have anemia (63.3%). This means that the risk of CED in pregnant women can be predicted based on the characteristics of young age, primipara, secondary education level, housewife's occupation, and although anemia does not occur.